General mechanisms for countering radio- ecological risks and disasters - Germenchuk, Maria (Journal of the Belarusian State University. Ecology, 2025)
The widespread use of nuclear energy for the purposes of scientific and economic progress, improving the quality of human life, solving other social or military problems, creates new sources of risks, threats and disasters of an anthropogenic nature (radioecological disasters), the consequences of which can be aggravated by natural disasters (environmental, hydrometeorological, seismological, others). In recent decades, there has been a rapid increase in the number of sources of risks and the scale of the consequences of disasters caused by radioecological risks. The international community, in order to meet the global challenge of confronting and improving preparedness for disaster response within the framework of the Hyogo and Sendai framework for action, has developed common approaches for the formation of risk management mechanisms that are also applicable to the management of radioecological risks. It is shown that the Republic of Belarus is successfully implementing the main priorities of the Hyogo and Sendai framework for action, including in the form of an External Emergency Response Plan for the Belarusian NPP. It was especially noted that at the present stage, the systemic introduction of preventive increases the potential of the Republic of Belarus in terms of countering radioecological disasters, including through the automatization of early warning systems, including using IT and AI technologies. The Algorithm of actions for risk management in the field of radiation safety in the Republic of Belarus was presented, providing for the functioning of mechanisms for managing radiological/radioecological risks:
Keywords: radiation safety; potential for confronting radioecological risks and disasters; Hyogo and Sendai framework for action; early warning